COVID-19, Profitabilitas, dan Kebijakan Dividen: Uji Robustness untuk Model Mediasi Menggunakan SEM Berbasis Kovarian - Powell Gian Hartono; Georgina Maria Tinungki; Kiandra Putri Susanto (International Journal of Digital Entrepreneurship and Business, 2023)
This study aims to test the mediating effect of profitability on the COVID-19 pandemic crisis toward dividend policy in Indonesia. The study was conducted between 2014 and 2020, with samples selected from real estate, property, and construction companies using a purposive sampling technique with pre-determined criteria. Furthermore, covariance-based structural equation modeling was used as the statistical analysis tool to test causality, and a robustness test was conducted on two empirical model approaches. The results showed that the COVID-19 pandemic crisis had a positive effect on profitability, which in turn had a positive effect on dividend policy. In the mediation test, the crisis positively affected dividend policy significantly mediated by profitability. This shows that real estate, property, and construction companies in Indonesia tend to reduce dividend levels during the crisis. Therefore, the management needs to pay attention to the mediating effect of profitability to determine dividend policy during a problem optimally. Investors also need to consider the mediating effect of profitability to obtain optimal returns in the form of dividends, specifically for real estate, property, and construction companies.